2021
DOI: 10.1186/s12870-020-02795-5
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose-phosphate phosphatase from sugarcane reveals an ancestral tandem duplication

Abstract: Background Sugarcane is capable to store large amounts of sucrose in the culm at maturity hence it became a major source of sucrose for the food and the renewable energy industries. Sucrose, the main disaccharide produced by photosynthesis, is mainly stored in the vacuole of the cells of non-photosynthetic tissues. Two pathways are known to release free sucrose in plant cells, one is de novo synthesis dependent on sucrose phosphate synthase (SPS) and sucrose phosphate phosphatase (S6PP) while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Our results revealed downregulation in the expression of SPP in apical culms at almost all time points. This result is in agreement with Partida et al (2021) , who reported downregulation of SPP 2D over the period of three to 12 months in source tissues of sugarcane. In any case, we did observe differences in temporal expression, which likely can be associated with the maturation of the genotypes in T4.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results revealed downregulation in the expression of SPP in apical culms at almost all time points. This result is in agreement with Partida et al (2021) , who reported downregulation of SPP 2D over the period of three to 12 months in source tissues of sugarcane. In any case, we did observe differences in temporal expression, which likely can be associated with the maturation of the genotypes in T4.…”
Section: Discussionsupporting
confidence: 93%
“…We also considered the relevance of genotypes to previous genomic studies. Hybrids SP80-3280 and R570 have been widely used in genomic studies and IN84-58 is a commonly used representative of S. spontaneum ( Partida et al, 2021 ). Genotype F36-819 is an important ancestor in Brazilian breeding programs, found in the pedigree of RB867515 ( Barreto et al, 2019 ), currently one of the most grown cultivars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABC, lipid, amino acid and sugar transporters were identified in the meta-QTL regions. The ABC transporter is known to transport fatty acid/lipids [39,40]. The sugar is mainly synthesized in leaves by the process of photosynthesis [41] and then transported to different storage tissues in the form of sucrose [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the model plant P. patens was adopted as a case for investigation. In order to demonstrate the workflow potential proposed here for multicopy gene studies, we investigate the expression of the six thiamine thiazole synthase (THI1) (Dias et al, 2023a(Dias et al, , 2023b and five sucrose 6-phosphate phosphohydrolase (S6PP) (Partida et al, 2021) paralogs genes as a proof of concept. It highlights the significance and implications of identifying the appropriate orthologous genes among the multicopy gene family.…”
Section: Case Study In the Moss Physcomitrium Patensmentioning
confidence: 99%